1983
DOI: 10.1007/bf00333299
|View full text |Cite
|
Sign up to set email alerts
|

Hamartomas of the tuber cinereum

Abstract: The hamartoma of the tuber cinereum, a midline dysraphic syndrome, corresponds to a mass of normal neuronal tissue implanted in the area of the mamillary bodies. It has no evolutionary potential, but association to other cerebral malformations has been observed. On the basis of 18 personal cases and a review of the literature, the authors evaluate the actual diagnostic criteria and the incidence of different clinical signs such as precocious isosexual puberty, seizures, and mental impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(30 citation statements)
references
References 25 publications
1
28
0
1
Order By: Relevance
“…An association between the size of the hamartoma and the presence of seizures has been proposed. Diebler and Ponsot [4] suggested that voluminous hamartomas distort the mammillary region, a part of the limbic system, and may initiate specific seizures.…”
Section: Discussionmentioning
confidence: 99%
“…An association between the size of the hamartoma and the presence of seizures has been proposed. Diebler and Ponsot [4] suggested that voluminous hamartomas distort the mammillary region, a part of the limbic system, and may initiate specific seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Other series have reported no change in follow-ups of up to 1 1 years [25][26][27]. Downloaded from www.ajronline.org by 54.191.190 …”
Section: Hypothalamic Hamartomamentioning
confidence: 92%
“…They may arise, however, from the floor of the third ventricle, or may lie free in the interpeduncular fossa [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Slow growth has been described in these tumors [14], but this has not been our experience.…”
Section: Hypothalamic Hamartomamentioning
confidence: 99%
“…In questi casi la RM risulta la metodica di studio di elezione 5 • Nella caratterizzazione della componente endo-orbitaria l'im-A piego della RM con sequenze per la saturazione del grasso, determinando un abbattimento dell'elevato segnale adiposo ed una riduzione degli artefatti da chemical shift, permette una ottima visualizzazione del nervo ottico e delle sue alterazioni morfologiche e di segnale. Tale vantaggio risulta ancora piu apprezzabile quando si abbini la 8 somministrazione endovenosa del Gd-DTPA.…”
unclassified